2001
DOI: 10.1677/erc.0.0080183
|View full text |Cite
|
Sign up to set email alerts
|

Studies of epidermal growth factor receptor inhibition in breast cancer.

Abstract: Until recently, there has been little knowledge on the growth control of oestrogen receptor (ER)-negative ductal carcinoma in situ (DCIS) and invasive breast cancer. The recent development of DCIS models, such as transgenic mice, cell-line xenograft models and, importantly, in vivo human DCIS xenograft models has facilitated the investigation and understanding of the control of growth of early pre-invasive breast lesions.Recent studies have shown that ER-negative DCIS, unlike ER-positive DCIS, is hormone indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…ZD1839 (Iressa, gefitinib) has proven to be useful preclinically and clinically for treating EGFR-expressing tumors, such as non-small cell lung cancer, head and neck cancer, breast cancer, prostate cancer, and others; the general doses used clinically are 250 to 500 mg/d (27)(28)(29)(30). Other EGFR inhibitors, such as Herceptin (trastuzumab), an anti-HER2 monoclonal antibody, have shown activity in a subset of breast cancers (31).…”
Section: Discussionmentioning
confidence: 99%
“…ZD1839 (Iressa, gefitinib) has proven to be useful preclinically and clinically for treating EGFR-expressing tumors, such as non-small cell lung cancer, head and neck cancer, breast cancer, prostate cancer, and others; the general doses used clinically are 250 to 500 mg/d (27)(28)(29)(30). Other EGFR inhibitors, such as Herceptin (trastuzumab), an anti-HER2 monoclonal antibody, have shown activity in a subset of breast cancers (31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ER-negative ductal carcinoma in situ express EGFR and HER-2 (Bundred et al, 2001) which are suggested to be the main receptor pathway associated with epithelial proliferation and survival in the human breast.…”
Section: Discussionmentioning
confidence: 99%
“…These mutual interactions between ER and HER pathways seem to hot-wire the events inducing endocrine resistance in ER-positive breast tumors [17, 18]. For all these reasons, HER-1/EGFR is thought to represent not only a possible prognostic marker but primarily a rational molecular target for a new class of anticancer agents [19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%